Informality vs Politics; The Interactions Between Politics and Social Behavior in Albania, a Retardment for the EU Integration Process - Demalija, Rifat (European Journal of Multidisciplinary Studies, 2017)
Is there a causal link for the acceptance of the informality between political class and social behavior? This paper intends to tackle this question exploring the retardment of the integration process and social actors’ behavior in Albania. In this regard, it is very important to understand the high level of informality in Albanian economy, social behavior and the nature of acceptance by political class. Despite the high level of informality, the will of Albanians to join EU remain high. According to the latest opinion polls, 86. 5 percent of the Albanians would vote in favor of the EU integration, the largest percentage in the EU integration aspiring countries. Political class, majority and opposition both, accuses each other for the retardment of the integration process, to get the highest support of voters, without bringing concrete solution for the informality and changing the situation. Informality in Albania continues to be a big concern for International Institutions which have been supporting and assisting the state institutions towards the formalization of economy. According to CIA World Factbook, the informality in Albania may be as large as 50 percent of official GDP during last five years. Regardless of the high level of the informality, government representatives and economy analysts argue that Albania is a country that is not affected directly by the crisis. One of the main factors which help the development of the informality in Albania is the widespread corruption, low level of enforcement, bureaucracies in the administration, politicized administration, habitual change of legislation and electoral promises to change the tax system, citizen’s interest for evasion and their adaptability. Another good example to argue our claim regarding the social behavior and links with politics is connected with the non-payment of the electricity not only by citizens, but also by state institutions. In contrast of formal social interaction of different social actors, informality should be read as social disorganization and one of the main obstacles that causes the retardment of the integration process. Keywords: informality, integration, politics, interaction, social behavior. 1.
Keywords: words: informality, integration, politics, interaction, social behavior. 1.